Host preference of the chinch bug, Blissus occiduus - Eickhoff, Thomas E. (University of Wisconsin Library, 2006)
The chinch bug, Blissus occiduus Barber (Hemiptera: Blissidae), is an important pest of buffalograss, Buchloë dactyloides (Nutall) Engelmann and potentially other turfgrass, crop, and non-crop hosts. Choice studies documented the number of B. occiduus present on selected turfgrasses, crops and weeds, and provided important insights into the host preferences of this chinch bug. Grasses with the most chinch bugs present included the warm-season turfgrasses B. dactyloides, zoysiagrass, Zoysia japonica Steudel, bermudagrass, Cynodon dactylon (L.) Pers., and St. Augustinegrass, Stenotaphrum secundatum (Walt.) Kuntze. The other grasses tested, green foxtail, Setaria viridis (L.) Beauv, Kentucky bluegrass, Poa pratensis L., perennial ryegrass, Lolium perenne L., rye, Secale cereale L., sorghum, Sorghum bicolor (L.) Moench, tall fescue, Festuca arundinacea Schreb. and wheat Tritium aestivum L. had significantly fewer chinch bugs. Buffalograss and zoysiagrass had the highest numbers of chinch bugs among the warm-season grasses and the buffalograss cultivars ‘86–120’ and ‘PX-3-5-1’ had more chinch bugs than the zoysiagrass cultivars ‘Meyers’ and ‘El Toro’ after the two hour evaluation time.